2010
DOI: 10.1515/shll-2010-1069
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Spanish Vowel Production: An Acoustic Analysis

Abstract: Findings from a cross-sectional study of the Spanish vowel productions of sixty adult second language learners of Spanish are presented in this article. The data set is based upon digitally recorded readings of an authentic Spanish-language short story. An acoustic examination of F1 and F2 values was carried out on twenty tokens of each vowel, 10 in stressed syllables, 10 in unstressed. The findings show that learners in the early stages of their Spanish study struggle to produce vowels in a native-like way, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 17 publications
0
30
1
Order By: Relevance
“…Changes in the F2 of L2 vowels due to stress were not clear-cut. Phonetic vowel reduction has been shown in other studies with heritage Spanish speakers (Ronquest, 2013), late Spanish-English bilinguals (Menke and Face, 2010;Rallo Fabra, 2015), English learners of L2 Spanish (Cobb and Simonet, 2015), and native English speakers (Fourakis, 1991), but only for nonfinal vowels.…”
Section: L2 Acquisition Of Spanish Stress By Native English Speakersmentioning
confidence: 56%
See 2 more Smart Citations
“…Changes in the F2 of L2 vowels due to stress were not clear-cut. Phonetic vowel reduction has been shown in other studies with heritage Spanish speakers (Ronquest, 2013), late Spanish-English bilinguals (Menke and Face, 2010;Rallo Fabra, 2015), English learners of L2 Spanish (Cobb and Simonet, 2015), and native English speakers (Fourakis, 1991), but only for nonfinal vowels.…”
Section: L2 Acquisition Of Spanish Stress By Native English Speakersmentioning
confidence: 56%
“…Menke and Face (2010) reported that English-speaking learners of Spanish had some tendency towards centralization of unstressed vowels. In addition, Cobb and Simonet (2015) reported evidence of phonetic vowel reduction of some Spanish vowels not only in L1 English/L2 Spanish speakers, but also in native Spanish speakers.…”
Section: L2 Acquisition Of Spanish Stress By Native English Speakersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Alvord and Christiansen (2012) observed that students who had lived abroad for an extended period of time exhibit much better pronunciation ofthe Spanish spirants [ß, Ô, y] than those who have not been abroad. Face and Menke (2009) and Menke and Face (2010) also found that very advanced students who had been abroad produced more Spanish-like vowels and consonants than less advanced students who had not spent time abroad. Lord (2006) showed that students improve in their phonological memory after just 7 weeks abroad.…”
Section: Pronunciation In Language Classrooms and Study Abroadmentioning
confidence: 97%
“…Investigations of the production of Spanish vowels by native English speakers have shown that learners tend to substitute English vowels for Spanish vowels (Morrison 2003(Morrison , 2006, to reduce Spanish vowels in unstressed syllables (Menke & Face 2010, Rafat & MacLeod 2010, and to use a smaller proportion of the acoustic vowel space than native speakers (Menke & Face 2010, Reeder 1998. While these studies provide important insights into the process of acquiring the vocalic inventory of Spanish, they have left unaddressed the acquisition of sequences of two vowels, which can be syllabified as either a diphthong (monosyllabic glide + vowel sequences) or a hiatus (disyllabic vowel + vowel sequences).…”
Section: Introductionmentioning
confidence: 99%